220 REDUCED-INTENSITY CONDITIONING USING ALEMTUZUMAB IN ALLOGENEIC HEMATOPOIETIC TRANSPLANTATION. Issue 1 (1st January 2007) - Arledge, S.; Elkins, S.; Bigelow, C.; Files, J.; Herrin, V.; Hardy, C.
Abstract : Purpose: Allogeneic hematopoietic transplantation after a myeloablative conditioning regimen has been shown to be an effective and potentially curative treatment for many hematologic malignancies due to the graft-versus-malignancy (GVM) effect. However, significant toxicities of such regimens have limited their use to younger, otherwise healthy patients. Reduced-intensity conditioning (RIC) transplantation has broadened eligibility to include older patients and those with comorbid conditions. RIC regimens using fludarabine and melphalan have been associated with a high risk of graft-versus-host disease (GVHD). Our institution adopted a RIC protocol that added alemtuzumab, an anti-CD52 monoclonal antibody that decreases T cells in the transplant recipient, to melphalan and fludarabine in an attempt to reduce the risk of GVHD while maintaining the GVM effect. Methods: From January 2005 to June 2006, 19 patients with hematologic malignancies received an allogeneic transplant using the RIC protocol. Median patient age was 52 years (34-66). Results: Acute and chronic GVHD occurred in 6 of 19 (31%) and 5 of 19 (26%), respectively, with only 17% of each being > grade II. Cytomegalovirus (CMV) reactivation occurred in 13 of 19 (68%). Seven of 19 (37%) patients experienced disease relapse or progression. One hundred-day survival was 79%. Ten of 19 (53%) have died at the time of this report. CMV infection was the probable cause of death in 3 of 10 (30%) deaths, or 16% of patients overall. Only one death was attributable to GVHD. Conclusions: RIC allogeneic transplant represents a reasonable treatment option for a variety of hematologic malignancies. There was a low incidence of severe GVHD and a 100-day survival of 79%. However, the mortality rate due to toxicity of this regimen was high at 37%. CMV infection represents a large proportion of this toxicity and provides an area to be improved upon in future RIC protocols, perhaps by using lower doses of alemtuzumab.